2016
DOI: 10.1159/000452842
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intraoperative Monitoring of Temporal Lobe Epilepsy Surgery

Abstract: Background/Aims: The monitoring of interictal epileptiform discharge rates (IEDRs) all along anterior temporal lobe resections (ATLRs) has never been reported. Here the effect of ATLR on continuous IEDR monitoring is described. Methods: IEDRs computed automatically during entire interventions were recorded in 34 patients (38.2%, 13/34 depth; 61.8%, 21/34 scalp electrodes only). Monitorings were invalidated when burst suppression occurred or if initial IEDRs were <5. Results: Monitoring was successful for 69.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Several studies that utilized EEG-fMRI to study brain activity in patients with TLE consistently observed abnormal activity in an area corresponding with the PC ( 12 , 78 81 ). Additionally, various studies have reported excellent rates of seizure freedom following surgical resection of the PC ( 5 , 8 , 83 ). Laser interstitial thermal therapy is an alternative therapeutic option that has demonstrated good efficacy in the treatment of patients with medically refractory TLE ( 84 86 ); however, future studies should aim to define specific inclusion parameters for the PC within the distribution of LITT ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies that utilized EEG-fMRI to study brain activity in patients with TLE consistently observed abnormal activity in an area corresponding with the PC ( 12 , 78 81 ). Additionally, various studies have reported excellent rates of seizure freedom following surgical resection of the PC ( 5 , 8 , 83 ). Laser interstitial thermal therapy is an alternative therapeutic option that has demonstrated good efficacy in the treatment of patients with medically refractory TLE ( 84 86 ); however, future studies should aim to define specific inclusion parameters for the PC within the distribution of LITT ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrand et al found that patients with treatment resistant TLE had significant decreases in interictal epileptic discharge rates (IEDR) following anterior temporal lobe resection, specifically with resection of the superior temporal gyrus. Additionally, 100% of patients who underwent concomitant mesial resection remained seizure free at 12-month follow up ( 83 ); such findings strongly advocate for inclusion of both anterior and mesial temporal lobe structures in the parameters for surgical management of TLE patients.…”
Section: Role Of the Piriform Cortex In Epilepsymentioning
confidence: 99%
“…Neuronavigation must be used in a standard fashion for the first surgery and especially for the second surgery as the neuroanatomical landmarks may be greatly distorted. Intraoperative scalp EEG on the contralateral hemisphere is used by some teams to detect interictal spikes [ 1 , 24 , 25 ]. A large prospective observational study published in 2019 showed similar efficacy of endoscopic hemispherotomy compared with open hemispherotomy, with lower levels of blood loss and shorter postoperative hospital stay [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent contributions have highlighted the importance of delineating the spike onset and propagation path 30 , 31 and that the resection of the source of spike propagation is associated with good outcome 32 . During real time intraoperative monitoring of spikes in anterior temporal lobe resections, a gradual decrease of spikes was reported following superior temporal gyrus resection with continued decrease following en bloc removal of the lateral temporal pole 7 . Moreover, this immediate decrease in spikes was observed in ipsilateral and contralateral destinations of spike propagation from the resected epileptic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Epileptiform potentials have served as the main interictal biomarker of reference for the EZ during preoperative assessment 6 . Intraoperative interictal spike frequency has been shown to drastically decrease in real time following the resection of epileptic foci 7 . Although these epileptic spikes confer a high sensitivity for identification of the true EZ, they are limited by low specificity.…”
Section: Introductionmentioning
confidence: 99%